CAREER ADAPTABILITIES IN UNIVERSITY STUDENTS: EXAMINING THE PREDICTION OF CAREER GOAL FEEDBACK AND LIFE GOALS - Ozan KORKMAZ,; Oğuzhan KIRDÖK, (MOJES: Malaysian Online Journal of Educational Sciences, 2022)
The purpose of this research is to examine the predictive of career goal feedback and life goals on career adaptabilities. The research using the relational screening model, which is one of the quantitative research methods, was carried out on university students. The participants of the research group consist of 277 (175 women, 102 men) university students studying at a public university in a province in the Southeastern Anatolia Region (Turkey) in the 2017-2018 academic year. Personal information form, Career Goal Feedback Scale, Career Adapt-abilities Scale, and Life Goals Scale-Short Form were used as data collection tools in the study. The data were analyzed using Pearson Moments Multiplication Correlation and path analysis techniques. Research findings showed that career goal feedbacks and internal life goals are important predictors of career adaptabilities. The findings are discussed within the framework of the literature and suggestions are presented.